Postural Stability and Physical Activity of Workers Working at Height. Issue 4 (July 2018) - Cyma, Magdalena; Marciniak, Katarzyna; Tomczak, Maciej; Stemplewski, Rafał
The purpose of the study was to analyze the level of postural stability and physical activity of at-height workers. The study included 34 healthy men aged 25–43. Two groups were identified based on the type of work they performed: at-height workers (HW) ( n = 17), and office workers (OW) ( n = 17). Physical activity, including physical activity at work, sports activity, and leisure, was assessed with a Baecke questionnaire. For evaluation of postural stability, the one-leg standing test with eyes open and closed was used. The HW group had a higher rate of average physical activity at work than the OW group ( p = .000), whereas the OW group showed greater physical activity during leisure time ( p = .000). No differences were found between the groups in terms of sports activity. Postural stability analysis shows that the HW group ( p < .05) scored statistically significantly higher values in one-leg standing with eyes closed. The groups differed in terms of postural stability in favor of HW. At the same time, despite differences in particular aspects, the overall level of PA was similar. This may indicate that postural stability is rather affected by exposure to distress conditions.